Trypanosoma cruzi I and IV stocks from Brazilian Amazon are divergent in terms of biological and medical properties in mice. - Wuelton Marcelo Monteiro; Ana Paula Margioto Teston; Ana Paula Gruendling; Daniele dos Reis; Mônica Lúcia Gomes; Silvana Marques de Araújo; Maria Terezinha Bahia; Laylah Kelre Costa Magalhães; Jorge Augusto de Oliveira Guerra; Henrique Silveira; Max Jean de Ornelas Toledo; Maria das Graças Vale Barbosa (Public Library of Science (PLoS), 2013)
Background In the Brazilian Amazon, clinical and epidemiological frameworks of Chagas disease are very dissimilar in relation to the endemic classical areas of transmission, possibly due to genetic and biological characteristics of the circulating Trypanosoma cruzi stocks. Twenty six T. cruzi stocks from Western Amazon Region attributed to the TcI and TcIV DTUs were comparatively studied in Swiss mice to test the hypothesis that T. cruzi clonal structure has a major impact on its biological and medical properties. Methodology/principal findings Seventeen parameters were assayed in mice infected with 14 T. cruzi strains belonging to DTU TcI and 11 strains typed as TcIV. In comparison with TcI, TcIV stocks promoted a significantly shorter pre-patent period (p<0.001), a longer patent period (p<0.001), higher values of mean daily parasitemia (p = 0.009) and maximum of parasitemia (p = 0.015), earlier days of maximum parasitemia (p<0.001) and mortality (p = 0.018), higher mortality rates in the acute phase (p = 0.047), higher infectivity rates (p = 0.002), higher positivity in the fresh blood examination (p<0.001), higher positivity in the ELISA at the early chronic phase (p = 0.022), and a higher positivity in the ELISA at the late chronic phase (p = 0.003). On the other hand TcI showed higher values of mortality rates in the early chronic phase (p = 0.014), higher frequency of mice with inflammatory process in any organ (p = 0.005), higher frequency of mice with tissue parasitism in any organ (p = 0.027) and a higher susceptibility to benznidazole (p = 0.002) than TcIV. Survival analysis showing the time elapsed from the day of inoculation to the beginning of the patent period was significantly shorter for TcIV strains and the death episodes triggered following the infection with TcI occurred significantly later in relation to TcIV. The notable exceptions come from positivity in the hemocultures and PCR, for which the results were similar. Conclusion/significance T. cruzi stocks belonging to TcI and TcIV DTUs from Brazilian Amazon are divergent in terms of biological and medical properties in mice.